(untitled) (Sustainability in Debate, 2016)
The goal of this article is to analyze the rationale of family farmers in decision-making processes involving a set of social technologies to be adopted in their properties, in a context of difficult access to water and food production in the Brazilian semiarid region. A case study of the project “Systematization and Reapplication of Social Technologies” was conducted, based on participatory observation, with the use of interviews and questionnaires. The project proposed the adoption of 14 different types of social technologies taken from different areas of the semiarid region by a group of 20 family farmers in the municipality of Piranhas, state of Alagoas (Brazil). Among the elements used by our subjects in the building of their rationale were: hardship, the availability of time, the availability of workforce, the availability of financial recources, the pursuit of improvements in quality of life, knowledge of nature in the semiarid, know-how about agricultural practices, and confidence in neighbors and relatives. Results suggest that family farmers develop and use a qualitative logical framework, closely associated with the their connection to the territory and to the strategies of interaction with the semiarid climate, informed by bonds of mutual trust.